split the middle term x2 - √2x - 12
it's X square and root 2x
Answers
Answered by
15
^_^
x² - √2 x - 12
=> x² - 3√2 x + 2√2 x - 12 = 0
=> x ( x - 3√2 ) + 2√2 ( x - 3√2 ) = 0
=> ( x - 3√2 ) ( x + 2√2 ) = 0
=> x = 3√2
And ,
x = - 2√2
^_^
x² - √2 x - 12
=> x² - 3√2 x + 2√2 x - 12 = 0
=> x ( x - 3√2 ) + 2√2 ( x - 3√2 ) = 0
=> ( x - 3√2 ) ( x + 2√2 ) = 0
=> x = 3√2
And ,
x = - 2√2
^_^
Similar questions
Sociology,
9 months ago
Math,
9 months ago
Computer Science,
9 months ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago